1982
DOI: 10.1679/aohc.45.285
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopic observations on single cilia in the intrahepatic biliary ducts in some birds.

Abstract: Summary. The intrahepatic biliary passage in five species of birds was investigated with the transmission electron microscope. The avian liver was characterized by a frequent occurrence of intralobular bile ductules and canaliculo-ductular junctions in the parenchyme. It was further characterized by solitary bile ductular epithelial cells intercalated among hapatocytes surrounding bile canaliculi.The present study first revealed that avian bile ductular epithelial cells possess a long single cilium. Its basal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The present electron microscopic study revealed the absence of the central microtubules, arms and spokes in the cilia of fat-storing cells. Therefore, the cilia of these cells are probably immotile, and likely play a role as a sensory or chemical receptor as such cilia are assumed to do in other types of cells (CURRIE and WHEATLEY,1966;OHATA et al, 1982b). Other authors have made the same assumption about the cilia of fat-storing cells (TANUMA et al, 1981;OHATA et al, 1984), although they could not demonstrate the axonemal ultrastructure.…”
Section: Methodsmentioning
confidence: 99%
“…The present electron microscopic study revealed the absence of the central microtubules, arms and spokes in the cilia of fat-storing cells. Therefore, the cilia of these cells are probably immotile, and likely play a role as a sensory or chemical receptor as such cilia are assumed to do in other types of cells (CURRIE and WHEATLEY,1966;OHATA et al, 1982b). Other authors have made the same assumption about the cilia of fat-storing cells (TANUMA et al, 1981;OHATA et al, 1984), although they could not demonstrate the axonemal ultrastructure.…”
Section: Methodsmentioning
confidence: 99%
“…There are few reports dealing with the ultrastructure of liver cells in herbivorous animals [1,2,9,[11][12][13].…”
Section: Abstract: Hepatocyte; Ultrastructure; Herbivoresmentioning
confidence: 99%
“…The bile capillaries are formed by membranes of contacting hepatocytes, but in the pigeon the bile capill~-~ is sometimes constructed by a membrane of one hepatocyte, as other authorities have also noted [12].…”
mentioning
confidence: 99%
“…The canaliculo-ductular junction is between the terminal of the bile capillary and ductile. It is lined with both hepatocytes and epithelial cells [12]. Because chicken and duck have gallbladders, their biliary plexus might have an important function to exchange materials with a small branch of the portal vein through the thin venous wall.…”
mentioning
confidence: 99%